AKTIVITAS TABIR SURYA DARI EKSTRAK FENOLIK PERIDERM UMBI UBI KAYU (Manihot Utilissima) - Karundeng, Glory (UNIVERSITAS SAM RATULANGI, 2014)
The objectives of this research are to determine the SPF value from periderm extract of yellow and white cassava tuber (Manihot utillisima). The SPF value is determined by spectrophotometry uv-vis. The result showed that the SPF value contained in yellow tuber is 15,5 while the white tuber is 11,3. Based on these results, periderm of yellow and white tuber possessed the potential as sunscreen. Â Keywords : SPF, Spectrophotometry uv-vis, Cassava Tuber Periderm Â